Consumer Interdependence via Reference Groups - Hayakawa, Hiroaki; Venieris, Yiannis (Journal of Political Economy, 1977)
In solving choice problems under bounded rationality, one relies on "heuristics" provided by social interdependence. Such "heuristics" consist in taking a particular social group as a reference group and in emulating its life-style by acquiring an associated cluster of complementary wants. A preference map generated by this reference-group-taking behavior exhibits smooth indifference curves which are convex to the origin with a "relevant range" over which the marginal rate of substitution is positive and diminishing. However, its implications on consumer choice and welfare economics are significantly different from those of traditional theory.